Konflikt jako wartość? Demokracja agonistyczna a populizm europejski w ujęciu Chantal Mouffe - Biały, Filip (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
One of the most intriguing questions in political philosophy has long been the following: how to organize politics that not only appeases the conflict of groups and individuals but also allows to express even irrational beliefs. The answer that this article has dealt with is a proposition by Chantal Mouffe, called ‘agonistic democracy’. The concept is based on an claim that the exclusion of an emotional component from the public sphere can only lead to a political conflict. An example that confirms Mouffe’s assumptions is the expansion of European populism, which, according to the theory discussed in the article, may only be contained through recognizing the positive value of the conflictive nature of politics.